The effects of heat stress on a number of hematological parameters and levels of thyroid hormones in foundry workers - Norloei, Sahar; Jafari, Mohammad Javad; Omidi, Leila; Khodakarim, Soheila; Bashash, Davood; Abdollahi, Mohammad Bagher; Jafari, Mina (International journal of occupational safety and ergonomics, 2017)
The objective of this research was to determine the effects of heat stress on some hematological parameters and thyroid hormones among foundry workers. This study was performed on 25 heat-acclimated subjects while 10 office workers were selected as the control group. Wet bulb globe temperature (WBGT) was determined to estimate the heat stress. Blood sampling was conducted before and after the daily work shift. The mean value of the WBGT index was 35 °C. The levels of plasma osmolality (p = 0.04) and white blood cells (p = 0.03) in the case group (before exposure to heat) were significantly higher than those in control group. No significant differences were observed between the average levels of T3 (p = 0.79) and T4 (p = 0.17) hormones between two groups. A positive relationship was found between the variation of some hematological parameters and thyroid hormones with WBGT index and air temperature.